Gambaran Program Kotaku ( Kota Tanpa Kumuh ) Kota Semarang Tahun 2019 (Studi Evaluasi Kebijakan) - Suharto Suharto (SOSIO DIALEKTIKA, 2021)
Management of housing and slum settlements is carried out in various forms of service and facilitation as follows: (1) fulfillment of decent and affordable housing needs through housing loans / subsidized housing loans and self-help housing development; (2) improving the quality of the settlement environment through the assistance of basic housing infrastructure and facilities, providing clean water facilities in water-prone settlements, structuring and rehabilitating slum settlements, empowering communities in the framework of strengthening economic capacity and improving social life; (3) institutionalizing a system for implementing housing and settlement development by involving the community as the main actor. Given the limited capacity of the government through the APBN and APBD in handling housing and slum settlements, the government took the decision to carry out handling of housing and slum settlements through the City Without Slum Program (KOTAKU). The implementation of the Tridaya approach in the KOTAKU program city of Semarang includes: (1) empowering local governments and communities through capacity building in the form of training and mentoring; (2) utilization of environmental facilities by improving the quality of the settlement environment through the procurement and repair of primary basic infrastructure and facilities as well as repair of unsuitable houses; and (3) community economic empowerment which is carried out through channeling with other programs in the field of Public Works and various activities carried out in the regions. To get a comprehensive picture of the program, researchers need to evaluate the policies of the Semarang City KOTAKU (City Without Slums) program in 2019.